Electrical Stapedial Reflex Thresholds in Cochlear Implant Recipients with Cochlear Nerve Deficiency: A Retrospective Study - Sasidharan, Megha; Kumar, Anil; Agarwalla, Pratik (International Archives of Otorhinolaryngology, 2025)
Cochlear nerve deficiency (CND) is characterized by a thin or absent cochlear branch of the vestibulocochlear nerve, leading to sensorineural hearing loss (SNHL). The effectiveness of cochlear implants (CIs) in patients with CND is debated, with some studies indicating poor outcomes and others showing limited speech detection and discrimination abilities. Accurate objective measures are essential for a successful CI mapping.To investigate the use of global stimulation with live speech to measure electrically evoked stapedial reflex thresholds (eSRTs) in CI recipients with CND and compare the results with behavioral comfort levels.This retrospective study reviewed the CI database from January 2015 to December 2023 to identify patients with CND. The eSRT measurements following CI were conducted using a standard procedure. These levels were compared with the behavioral comfort levels from their mapping data.From the CI database of 273 recipients, six children with CND were identified whose eSRT levels were documented. Among these six, two children exhibited presence of electrical stapedial reflexes that correlated well with behavioral comfort levels in response to global stimulation of electrodes. None of them presented reflexes to individual electrode stimulation.Global stimulation of electrodes has the potential to elicit eSRT in patients with CND more than individual electrode stimulation. Further research is crucial to validate the effectiveness of global stimulation in eliciting eSRT in a larger cohort of patients with CND. This would be a feasible test as an outcome measure, and it would help provide better prognostic counselling.
Keywords: cochlear nerve deficiency; electrical stapedial reflex; post operative; children; cochlear implant